Cálculo de equivalentes dinâmicos de sistema de potência usando algoritmos genéticos - SANTOS, Pitther Negrão dos (Universidade Federal do Pará, 2015)
This dissertation presents a genetic algorithm-based method for calculating of power system dynamic equivalents aiming to represent parts of a power system for transient stability analysis. The dynamic equivalent calculation is obtained through carrying out the parameter identification of synchronous generators located on frontier buses, linking the external and the studied subsystem. An index is used to assess the proximity between simulations carried out using the full and the reduced model following the large disturbances emerged in the studied subsystem. Different operating conditions are taken into account. The simulations were conducted using the softwares GAOT “The Genetic Algorithm Optimization Toolbox”,, ANAREDE and ANATEM. This method is tested on a Kundur’s two-area test system and on a Brazilian Interconnect Power System (BIPS). Test results validate the efficacy of the developed methodology in calculating the robust dynamic equivalents.